Transnational Enforcement Through the Indonesia–Singapore Extradition Framework Against Corruption - Wahyu Sinta Dewi Pramudita; Anis Widyawati (JURNAL USM LAW REVIEW, 2025)
This study examines the effectiveness of the Indonesia–Singapore extradition framework as a transnational law enforcement mechanism in combating corruption crimes with cross-border dimensions. The research is motivated by Indonesia’s longstanding challenges in recovering fugitives and assets located in Singapore, despite the existence of bilateral agreements and mutual legal assistance arrangements. Employing a normative juridical method with statutory, conceptual, and comparative approaches, this study analyzes the extradition treaty, implementing regulations, relevant case practices, and principles of international cooperation in criminal matters. The findings reveal that while the extradition framework provides a formal legal basis for cooperation, its practical implementation remains constrained by differences in legal systems, evidentiary standards, dual criminality requirements, and political considerations that may delay or impede extradition processes. Moreover, the effectiveness of extradition is closely linked to asset recovery mechanisms, which are not always synchronized with extradition procedures. The novelty of this study lies in its integrated analysis of extradition and transnational asset recovery within a single enforcement framework, highlighting the need for stronger procedural coordination and institutional synergy. This study recommends strengthening treaty implementation through clearer operational guidelines, enhanced mutual trust between law enforcement agencies, and closer alignment between extradition and asset recovery mechanisms to ensure effective, timely, and accountable transnational enforcement against corruption.